ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN ONLINE DI SMK IT RABBI RADHIYYA MASA PANDEMI COVID-19 - Julia Elisvi; Rafia Archanita; Deri Wanto; Idi Warsah (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2020)
Almost all circles of society in the world today are shadowed by an extraordinary fear of the plague that hits the world or the so-called the pandemic. In early 2020, Indonesia even also felt the same thing, and this has an implication for the issuance of several government policies in an effort to minimize the spread of the covid-19 outbreak by giving an appeal to the community to limit gatherings including school activities by switching them to the application of work from home (WFH) learning. In response to these conditions, many problems will arise and be faced by teachers, students, and parents. Departing from this phenomenon, this study aimed to find out the details of online learning at home undertaken by SMK IT Rabbi Radhiyya’s students using a qualitative approach. The data of this study were collected through observation, interview, and documentation techniques which were then analyzed to obtain a depiction of the online learning. This study concluded that the application of work from home (WFH) online learning during the covid-19 pandemic as a learning medium in SMK IT Rabbi Radhiyya ran smoothly. The depiction of learning was such as: The teacher gave assignments to students, and students worked on them via WhatsApp application and Google Classroom followed by collecting assignments in due course; Students memorized Al-Quran and Hadith and then sent the memorization videos with eyes closed to the teacher; the teacher gave an assignment for students to make videos about their busy routines during staying at home; and students made reports insofar as they were carrying out online learning at home.Keywords: Online Learning, Learning Media, Covid-19 Pandemic